Different Neural Systems Contribute to Semantic Bias and Conflict Detection in the Inclusion Fallacy Task - Liang, Peipeng; Goel, Vinod; Jia, Xiuqin; Li, Kuncheng (Frontiers in Human Neuroscience, 2014)
more general conclusion category is considered stronger than a generalization to a specific conclusion category nested within the more general set. Such inferences violate rational norms and are part of the reasoning fallacy literature that provides interesting tasks to explore cognitive and neural basis of reasoning. To explore the functional neuroanatomy of the inclusion fallacy, we used a 2×2 factorial design, with factors for Quantification (explicit and implicit) and Response (fallacious and nonfallacious). It was found that a left fronto-temporal system, along with a superior medial frontal system, was specifically activated in response to fallacy responses consistent with a semantic biasing of judgment explanation. A right fronto-parietal system was specifically recruited in response to detecting conflict associated with the heightened fallacy condition. These results are largely consistent with previous studies of reasoning fallacy and support a multiple systems model of reasoning.